СИСТЕМА БАГАТОВАРІАНТНОГО ПРОПОРЦІЙНО-ВЕКТОРНОГО УПРАВЛІННЯ ПАРАЛЕЛЬНИМ АКТИВНИМ ФІЛЬТРОМ ЧОТИРИПРОВІДНОЇ ТРИФАЗНОЇ СИСТЕМИ ЖИВЛЕННЯ - Артеменко, М.Ю.; Батрак, Л.М. (Інститут електродинаміки НАН України, Київ, 2014)
Multivariate proportional-vector control system for shunt active filter of three-phase four-wire power system was proposed. Depending on the application conditions one of the twenty control methods optimal for certain quality characteristics can be selected. References 6, figure 1.